Integración de Estrategias Pedagógicas Basadas en TIC y la Motivación para Aprender Ciencias Sociales en Secundaria Pública de Mexicali, México - Jesús Miguel Calvo Martínez; Francisco Javier Fernández Barrón (Ibero Ciencias - Revista Científica y Académica - ISSN 3072-7197, 2026)
This study analyzed the relationship between the integration of teaching strategies based on Information and Communication Technologies (ICT) and motivation to learn social sciences among third-grade students at a public middle school located in the western region of Mexicali, Baja California, during the 2025–2026 school year. The objective was to analyze this relationship, considering the frequency of use, planning, and diversity of the technological strategies employed. A quantitative approach was adopted, using a non-experimental, cross-sectional, correlational research design, with a sample of 100 students (n = 100). A 20-item Likert-scale questionnaire was administered, validated through expert judgment, and demonstrated good internal consistency (α = .857). Descriptive and inferential statistical analyses identified a positive, moderate, and statistically significant correlation (r = .432, p < .001) between the integration of ICT-based pedagogical strategies and student motivation, showing that greater pedagogical integration of these technologies was associated with higher levels of motivation. The findings confirmed that the pedagogical integration of ICT constitutes a relevant factor in fostering learning. The results supported strengthening instructional planning, continuous teacher professional development, and the design of dynamic and interactive digital learning activities. The study provided contextualized empirical evidence for Mexican public secondary education, strengthened knowledge in the field of Educational Technology, and provided a foundation for informing pedagogical decision-making and future research.